Serum vitamin D status is associated with the presence but not the severity of primary open angle glaucoma. Issue 4 (August 2015) - Goncalves, Aurélien; Milea, Dan; Gohier, Philippe; Jallet, Ghislaine; Leruez, Stéphanie; Baskaran, Mani; Aung, Tin; Annweiler, Cédric
Highlights Vitamin D is involved in visual health and function. Cases with glaucoma had lower mean serum 25OHD concentration than controls. There was no 25OHD difference between moderate and severe glaucoma. These findings provide a scientific base for vitamin D replacement trials.